If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c(c + -7) = 0 Reorder the terms: c(-7 + c) = 0 (-7 * c + c * c) = 0 (-7c + c2) = 0 Solving -7c + c2 = 0 Solving for variable 'c'. Factor out the Greatest Common Factor (GCF), 'c'. c(-7 + c) = 0Subproblem 1
Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0Subproblem 2
Set the factor '(-7 + c)' equal to zero and attempt to solve: Simplifying -7 + c = 0 Solving -7 + c = 0 Move all terms containing c to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + c = 0 + 7 Combine like terms: -7 + 7 = 0 0 + c = 0 + 7 c = 0 + 7 Combine like terms: 0 + 7 = 7 c = 7 Simplifying c = 7Solution
c = {0, 7}
| 13=g/3-(-11) | | 0=25-10x^2 | | -3+(-n)=-7 | | x^2-4x+9=2 | | 3x^2+40x-2000=0 | | 2=4+(-2p) | | 13-2b=1 | | 1200=18(5t-1.5) | | 8=2-(-2t) | | 15ab+[(6ab-c)+(4ab+c)]= | | 8=2-(-2) | | M=-1/2;(-3,0) | | M÷-1/2;(-3,0) | | 6=3r-(-3) | | 2-(-3p)=11 | | r/3-2=1 | | 2/3u-3/2=-1/5 | | 14=4k+2 | | v(v)+3v-18=0 | | 10(x-2)/5x-10 | | 3(4x+6)=9x+122 | | (5u-4)(3-u)=0 | | -6(c+1)-(6+5c)= | | (2x+3)+(4x+8)=180 | | =(y+6u)(7y-7u-5) | | -12x-20=-10x-15 | | -2x-10=3x-15 | | fn=5n+6 | | 16x-10+9=99-30x | | 6cosx+5=-5cosx+14 | | x+.05x=252000 | | (6x-5)(8x+3)=0 |